Pemberdayaan Remaja Mesjid Melalui Keterampilan Pembenihan dan Pembesaran Ikan Lele Sebagai Peluang Usaha dan Ketersediaan Pangan Keluarga di Kelurahan Sidodadi - Sudarwati, Lina; Dewinta, Astrid Fauzia; Andriani, Lusiana; Atika, Tuti; Supsiloani, Supsiloani (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Based on population data of Sidodadi Village in 2022, around 3107 people or 66.80% of the total population turned out to be unemployed and became dependents of 33.20% of the productive age population who worked. In addition to the high unemployment rate in Sidodadi Village, the fate of the younger generation is also threatened by the rampant drug use. The problem found is the absence of capital and the lack of skills to start a business. Based on the problems described earlier, community empowerment efforts for youth are needed. This Community Empowerment activity is carried out through stages starting with problemmapping, solution offering, training and business preparation practices, spawning training and practices, training and enlargement practices, digital marketing training, to evaluation and monitoring. A series of stages of empowerment activities have been completed and someforms of value changes that occurred after the empowerment was carried out, namely achange in orientation towards abandoned ponds that were originally considered useless can finally be used and utilized as a source of economic improvement through catfish farming. In addition, there is also achange in the assumption that working individually is more effective instead of working together in a team or group.